SERIES OF AGRICULTURE IN DATABASE OF THE STATISTICAL OFFICE OF THE REPUBLIC OF SERBIA - Radović – Stojanović, Jelena V.; Zečević, Aleksandra T.; Kojčin, Zorica D. (Economics of Agriculture, 2015)
The objectives of this Paper have been to examine which data on agriculture can be found in the Statistical Offce of the Republic of Serbia Database, and what are the possibilities for the use of the Database in the research and analysis of agriculture. The Statistical Offce of the Republic of Serbia Database physically represents normalized database formed in DBMS SQL Server. The methodological approach to the Paper subject is primarily related to modelling and the way of using Database. The options of accession, fltering and downloading of data from the Database are explained. The technical characteristics of the Database were described, indicators of agriculture listed and the possibilities of using Database were analysed. We examined whether these possibilities could be improved. It was concluded that improvements were possible, frst, by enriching Database with data that are now only available in printed publications of the Offce, and then, through methodological and technical improvements by redesigning the Database modelled on cloud founded databases. Also, the application of the achievements of the new multidisciplinary scientifc feld - Visual Analytics would improve visualization, interactive data analysis and data management.